Effects of whole-body vibration warm-up on subsequent jumping and running performance - Ewertowska, Paulina; Świtała, Katarzyna; Grzyb, Wojciech; Urbański, Robert; Aschenbrenner, Piotr; Krzysztofik, Michał (Scientific reports, 2023)
The aim of this study was to examine whether acute whole-body vibration, a single bout of drop jumps, or a combination of both may enhance countermovement jump (CMJ) and would affect volitional pace 3 km running performance. Twelve healthy and recreationally active males completed 4 conditions in randomized order: (i) 5 sets of 30 s calf raises on the platform but without vibration; (ii) 5 sets of 30 s calf raises on the vibration platform with 30 s rest intervals between sets; (iii) 5 sets of 6 drop jump with a 30 s rest interval between sets; (iv) 5 sets of 30 s calf raises on the vibration platform followed by 6 drop jumps with a 30 s rest interval between sets. Before, 3-min after, and immediately after a 3 km run each participant performed CMJ. No significant difference between conditions (p = 0.327) for the 3 km time trial was found. Whereas CMJ height and relative peak power were significantly improved in post-3 km run than at baseline (p < 0.001 and p = 0.025) and post-warm-up (p = 0.001 and p = 0.002) in all conditions. The present study indicates that warm-up consisting of either whole-body vibration, drop jumps, or a combination of both failed to acutely improve CMJ and 3 km volitional pace running performance in physically active males. However, the increase in the CMJ performance was noted after the end of the 3 km run, which may indicate that the warm-up protocols used were insufficient to enhance subsequent performance.
Keywords: Muscle, Skeletal; Vibration; kosterní svaly; Running; Rest; Humans; Warm-Up Exercise; běh; lidé; bérec; Athletic Performance; mužské pohlaví; Male; odpočinek; Leg; vibrace; zahřívací cvičení; sportovní výkon